Slot dipole antenna with single‐ and dual‐band tuning characteristic. Issue 21 (1st October 2014) - Idris, I.H.; Hamid, M.R.; Jamaluddin, M.H.; Rahim, M.K.A.; Kelly, J.
Abstract : A slot dipole antenna with a reconfigurable operating frequency is presented. The antenna comprises two pairs of slot arms. Each arm incorporates a number of varactor diodes. The antenna is capable of operating in single‐band or dual‐band mode. In each case, the location of these bands can be altered by varying the voltage applied to the varactor diodes. The antenna can be tuned over a wide frequency range, namely 1.5–4.5 GHz (i.e. a ratio of 3:1). The antenna is potentially useful for cognitive radio application, particularly in a small base station or access point terminal.